The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/ncomms11040
|View full text |Cite
|
Sign up to set email alerts
|

CETSA screening identifies known and novel thymidylate synthase inhibitors and slow intracellular activation of 5-fluorouracil

Abstract: Target engagement is a critical factor for therapeutic efficacy. Assessment of compound binding to native target proteins in live cells is therefore highly desirable in all stages of drug discovery. We report here the first compound library screen based on biophysical measurements of intracellular target binding, exemplified by human thymidylate synthase (TS). The screen selected accurately for all the tested known drugs acting on TS. We also identified TS inhibitors with novel chemistry and marketed drugs tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(153 citation statements)
references
References 36 publications
5
144
0
1
Order By: Relevance
“…However, compound-induced quenching of protein target recognition was observed by both our ELISA assay using several combinations of RIPK1 antibodies and a commercially available ELISA kit. This quenching effect has already been reported 4,24 and the effects on RIPK1 protein might be dependent on RIPK1 associated with a variety of proteins 14,15,25 . Therefore, we focused on establishing a widely used Western blotting method in a semi-automated procedure.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…However, compound-induced quenching of protein target recognition was observed by both our ELISA assay using several combinations of RIPK1 antibodies and a commercially available ELISA kit. This quenching effect has already been reported 4,24 and the effects on RIPK1 protein might be dependent on RIPK1 associated with a variety of proteins 14,15,25 . Therefore, we focused on establishing a widely used Western blotting method in a semi-automated procedure.…”
Section: Resultssupporting
confidence: 74%
“…All of the data are shown as mean ± SEM. For the T agg shift and the ITDR experiments, data were analysed in GraphPad Prism using the Boltzmann sigmoid equation and the four-parameter logistic curve 4,24 . Student’s t -test was used to calculate P values with Microsoft Excel.…”
Section: Methodsmentioning
confidence: 99%
“…Second, for compounds that need to be activated in the cell (prodrugs), the F ic of the dosed parent molecule might not be relevant. However, metabolically activated species can easily be monitored as well, such as we previously did for compounds targeting thymidylate synthase (31). Third, the method is designed to give information on exposure in the whole cell (i.e., an average of cytosolic and organelle exposure), which limits the resolution for targets located in specific subcellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary study with a single cytosolic target (thymidylate synthase), we showed that intracellular concentrations of active hits and reference drugs correlate with intracellular target engagement (31). We, therefore, hypothesized that F ic might be a practical metric for predicting compound access to intracellular targets.…”
mentioning
confidence: 99%
“…TS catalyzes the reductive methylation of deoxyuridylate (dUMP) to deoxythymidylate (dTMP) . As the TS pathway provides the sole de novo synthesis of dTMP, disrupting the pathway can significantly affect the cell viability . Accordingly, TS has been regarded as an important target against infectious diseases.…”
Section: Introductionmentioning
confidence: 99%